Benefits of Corporate Volunteering for Human Resources management - Licandro, Oscar Daniel; Yapor, Stefanía; Correa, Patricia (Revista Venezolana de Gerencia, 2021)
This document identifies the benefits of Corporate Volunteering for the management of Human Resources present in the scientific literature, they are organized into three categories (development of skills in employees, strengthening the link between them and the company, creating conditions that improve its performance) and the results of an investigation are presented, which had as objectives: a) to verify the occurrence of these benefits; b) determine if it depends on structural factors of the companies (size, sector of activity and origin of capital) and on factors related to volunteer management. It worked with a non-probabilistic sample of companies that apply volunteering in Uruguay, to which a structured questionnaire was applied that included eight indicators on benefits. It was found, through statistical tests, that the eight benefits are present in the experience of the companies studied and that their occurrence is independent of the profile of the companies, the way in which volunteering is managed in them and the alignment of volunteer activities with Human Resources policies.